Institutional Collection Center of Una Sustainable Campus, and its Contribution to the Conservation and Environmental Protection from a Gender Perspective - Rojas Vargas, Julian Alberto (2017)
The article describes the contribution from a gender perspective the Institutional Collection Center, UNA (National University of Costa Rica) Sustainable Campus of the National University of Costa Rica, makes for the conservation and environmental protection. It also describes the good practices that are developed there in the field of environmental management, and tools both for the student community, teachers, and administrative staff. The Center contributes to the performance and environmental protection. Besides, it promotes the strengthening of environmental culture in the university community. Through the different projects, students involved can collaborate and generate environmental changes, through chats and forums on this topic, as well as collecting and classifying waste. Emphasis is placed on the policies of environment and gender that the National University owns, scope and plans of action, as well as the important equitable participation between university populations in all spaces.